The Role Of Internal Auditing And Internal Control System On The Financial Performance Quality In Banking Sector - Ali Kadhim, Hussein Al-Fatlawi (Opción, 2019)
The objective of the empirical study is to examine and analyze the influence of internal audit and internal control systems on the prevention of accounting fraud in banking sector. This study obtained data from primary data. The sample of this empirical study is an employee who works in the three largest banks in Indonesia and has working experience at least two years. This research uses multiple linear regression analysis as hypothesis testing. The results of the empirical study are (1) internal audit had a positive significant influence on the prevention of accounting fraud in banking sector, (2) internal control system had a positive significant influ- ence on the prevention of accounting fraud in banking sector.